PENGARUH LATIHAN BENCH PRESS TERHADAP KEKUATAN OTOT LENGAN SISWA PUTRA EKSTRAKURIKULER BOLAVOLI SMP NEGERI 29 PEKANBARU - Andriani, Popi; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observation that has been done when students attend extracurricular activities volleyball in SMP 29 Pekanbaru, it appears that the strength of the arm muscles students are still weak, it is not visible from the maximum results service ball, the ball is often caught in the net, sometimes the ball does not get field opponent. Then when students receive service from an opponent by way of passing down, weak arm muscle strength resulting in a ball that is received can not be dipassing well. Then smash the weak punch also signifies that the student arm muscle strength is still low, so the balls that dismash acceptable opponent and counterattack. the low student arm muscle strength caused by the absence of the application of physical exercise, especially exercises that increase the strength of the arm muscles. The purpose of this study was to look at the effects of exercise on muscle strength bench press arm male student extracurricular volleyball SMP 29 Pekanbaru. As the population used in this study were male student extracurricular volleyball SMP 29 Pekanbaru totaling 16 people. The sampling technique used is saturated sample that is where all the population sampled. Thus the sample in this study amounted to 16 people. The instrument used to collect data is Pree test and post-test muscle strength with test arm push-ups. The data obtained was analyzed using t-test. Based on the results of data analysis, Pree test and post-test, it appears that there is an average increase of 38.07% with a t test that t = 9.958> from table = 1,753.Key Words: Exercise Bench Press, Arm Muscle Strength